JUDICAL PROTECTION OF WHISTLEBLOWERS - Gavranić, Ratko (Glasnik Advokatske komore Vojvodine, 2025)
The Law on the Protection of Whistleblowers of the Republic of Serbia has been applied in judicial practice for almost ten years. Inspired by this fact, the author, relying on the existing normative framework and stances of judicial practice, addresses key issues significant for the judicial protection of whistleblowers. These issues relate to the application of the Law on the Protection of Whistleblowers, the time limits for the protection of whistleblowers, the passive standing in whistleblower protection proceedings, judicial jurisdiction, the existence of a causal link between whistleblowing actions and harmful actions, and finally, temporary measures for the protection of whistleblowers as the most effective means of their protection. To analyze the application of the Law throughout the territory of the Republic of Serbia, the paper examines the practices of all four appellate courts in the country, as well as that of the Supreme Court.